The Comparison Between Growth Mindset and Fixed Mindset in Their Influence on Academic Achievement - Putri, Nabella Andryani; Sukatin; Amalia Trianita Wilman (MUNTAZAM, 2023)
The influence of growth mindset and fixed mindset on academic achievement is significant. Mindset shapes actions and interpretations, with two main types: fixed and growth mindsets. The fixed mindset assumes unchangeable abilities, while the growth mindset believes in potential through effort and learning. These mindsets result in different responses to failure. Fixed mindset individuals see failure as a lack of talent, leading to despair and giving up. Conversely, those with a growth mindset perceive failure as an opportunity to learn and grow. Nurturing a growth mindset in children is crucial for resilience and determination in overcoming challenges. This study employs qualitative methods to explore how mindset impacts academic achievement and educational practices.